Essays on violence : Pollution sacrifice and madness - Vijaisri, Priyadarshini (New Delhi : Bloomsbury, 2024)
Essays on Violence: Pollution, Sacrifice and Madness is an exploration of the intersecting histories of caste and violence in the Indian context foregrounding ideational and temporal continuities and deep linkages between ideas, processes and events by combing historical sources with ethnographic data. Traversing the diverse and conflicting strands in Indian traditions, it traces the centrality of the idea of violence in discourses on sacrificial violence, self, body, evil and danger and their reverberations in critical moments of Indian history. The discourse on caste violence is unpacked through analysis of concepts like danda, matsyanyaya and vadhoavadha, religious and textual exegesis of negation and demonization and historical sites to locate processes of transitions in cultures of violence via the Telangana armed uprising and imagined cartography of the incipient nation. By drawing attention to the nature of caste violence in postcolonial Andhra, the book offers glimpses into the emergence of contradictory pulls in the forging of caste identities, nationhood and the shifts in the subjectivity of outcastes within the context of repressive political culture of postcolonial democratic experience.
Keywords: History / Asia / General; History / Asia / South / India; History / Social History